2022
DOI: 10.3390/antiox11071215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Density on the Growth Performance, Physiological Parameters, Redox Status and Lipid Metabolism of Micropterus salmoides in Integrated Rice–Fish Farming Systems

Abstract: Stocking density has been identified as one of the main factors affecting fish growth, welfare and behavior. However, few studies have focused on the effects of stocking density on fish health in integrated rice–fish farming systems. Thus, the aim of this study was to evaluate the effects of different stocking densities on the growth performance, physiological parameters, redox status and lipid metabolism of Micropterus salmoides in an integrated rice–fish farming system. The fish were reared at three densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 96 publications
1
8
0
1
Order By: Relevance
“…Hence, it is generally recognized that the content of MDA can reflect the level of oxidative damage in organisms ( Han et al, 2022 ). It has been reported that the content of MDA significantly increased with the increasing stocking density in many aquatic animals, such as M. salmoides ( Jia et al, 2022 ), S. maximu ( Jia et al, 2016 ), and blunt snout bream ( Megalobrama amblycephala ) ( Wang et al, 2018 ). In this study, the significant increase of MDA content in the HD group also proved that long-term high stocking density caused oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is generally recognized that the content of MDA can reflect the level of oxidative damage in organisms ( Han et al, 2022 ). It has been reported that the content of MDA significantly increased with the increasing stocking density in many aquatic animals, such as M. salmoides ( Jia et al, 2022 ), S. maximu ( Jia et al, 2016 ), and blunt snout bream ( Megalobrama amblycephala ) ( Wang et al, 2018 ). In this study, the significant increase of MDA content in the HD group also proved that long-term high stocking density caused oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Under a high stocking density, glucose metabolic enzymes were activated, which enhanced energy production to resist the environment stimuli in abalone ( Haliotis discus hannai ) ( Gao et al, 2018 ). A transcriptomic analysis of M. salmoides indicated that high stocking density caused abnormal lipid metabolism ( Jia et al, 2022 ). In line with previous studies, our data also showed that the metabolic function of hepatopancreas, such as organonitrogen compound catabolic process, proteolysis involved in cellular protein catabolic process, modification-dependent protein catabolic process and cellular protein catabolic process, was significantly influenced by high stocking density.…”
Section: Discussionmentioning
confidence: 99%
“…19 Understanding the bioavailability of DHPV aer PACs oral intake is of paramount importance for harnessing their health benets and designing functional food products. [20][21][22][23][24] In this regard, quantitative bioanalytical methods based on stable isotopically labelled (SIL) analogs represent a valuable tool to pursue these goals. In particular, the use of isotopic labelled internal standard in mass spectrometry allows to have the best results in terms of precision and accuracy when quantifying the unknown amount of molecule of interest in a biological matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Stocking density is an important factor determining the profitability of an aquaculture venture and farmers tend to increase stocking with the aim of increasing productivity (Oke and Goosen 2019). High stocking density has been shown to produce a chronic stress situation in Gilthead sea bream (Jia et al 2022), the same husbandry practice has also been shown to induce chronic stress which elevates the levels of plasma cortisol and glucose in O. niloticus (Aketch et al 2014).…”
Section: Introductionmentioning
confidence: 99%